Tinjauan Yuridis Terhadap Penyalahgunaan Kendaraan Dinas Operasional di Kabupaten Wajo - Yustiana; Jumasniayanti; Wahyudi, Kadek Ari; Arifin, Irfan; Afnan, Andi Muhammad; Suhariadi, Ahmad (YP-SDI Lamaddukelleng, 2024)
This research aims to take a deeper look at the misuse of official vehicles, including the causal factors, impacts, and solutions that can be implemented to overcome this problem. Referring to the Minister of Finance Regulation Number 172/PMK.06/2020, it is explained that official vehicles can be obtained after occupying Echelon IV and or equivalent positions, or becoming head of an office in a work area of at least 1 (one) district (city). Official vehicles are expected to assist state civil apparatus employees in carrying out their duties and it is hoped that official vehicles will be used only for purposes related to the duties and obligations of state civil apparatus. Official vehicles are one of the many facilities provided by the state to government employees to function as stated in the law. However, there are still many state civil apparatus employees who abuse these facilities. The approach method used is empirical juridical, with a problem approach using a system of laws and regulations, concepts, and analytical approaches. Law enforcement for ASN and non-ASN employees who misuse official vehicles in Wajo Regency has not been effective, even though official vehicles are roaming on holidays, there has been no government action in sanctioning the misuse because there are no regulations that clearly regulate the misuse of operational official vehicles. The impact is that official vehicle users do not really understand how official vehicles are used according to official functions